1998
DOI: 10.1093/oxfordjournals.deafed.a014356
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Route for Preparing Deaf Children for BiBi Programs: The Home Language as LI and Cued Speech for Conveying Traditionally-Spoken Languages

Abstract: This article focuses on nonsigning hearing parents of deaf children who share the goals of bilingual-bicultural (BiBi) programs for their child, opt for their home language to be their deaf child's first language (L1), and have questions about communication options (e.g., oral methods, manually coded English [MCE] systems, or Cued Speech) for conveying that language. We present research findings related to the effectiveness of MCE systems and Cued Speech for conveying English and developing deaf children's rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…All participants completed a generative rhyming task, adapted from that used by Hanson and McGarr (1989) and LaSasso and Metzger (1998). Participants had to write as many words as possible that rhymed with a given target written word.…”
Section: Introductionmentioning
confidence: 99%
“…All participants completed a generative rhyming task, adapted from that used by Hanson and McGarr (1989) and LaSasso and Metzger (1998). Participants had to write as many words as possible that rhymed with a given target written word.…”
Section: Introductionmentioning
confidence: 99%
“…One empirical study on signed English systems showed that users were not highly consistent in their morphological productions (Supalla, 1991). The combination of ASL and English languages in this artificial manner requires substitutions in language features, but these substitutions have the effect of eliminating parts of each language so that native users of MCE are not fluent in either ASL or English (Ramsey, 1989; LaSasso and Metzger, 1998; Drasgow and Paul, 1995). For ASL, what is missing are the ASL‐based structure and grammar, which are expressed spatially in signed language rather than in a sequentially spoken string.…”
Section: Native Cae Vs English‐as‐l2 In the American Deaf Communitymentioning
confidence: 99%
“…The children attempting to acquire English therefore do not have access to a continuous stream of phonemes, nor do they have consistent opportunities to interact with fluent users of the language in the early years. Because of these gaps, children who are taught SEE II do not score any better on standardized reading tests than do most children who are raised with ASL as a first language (LaSasso and Metzger, 1998; Drasgow and Paul, 1995).…”
Section: Native Cae Vs English‐as‐l2 In the American Deaf Communitymentioning
confidence: 99%
“…Another study showed the way that family members communicate can determine deaf children's self-esteem. Hence, it can be interpreted that when deaf children belong to a group, their self-esteem increases (LaSasso& Metzger, 1998). This study only refers to the type of parent's communication.…”
mentioning
confidence: 99%